Takotsubo syndrome in a patient with atrial fibrillation after electrical cardioversion: a case report - E. S. Sitkova; A. V. Smorgon; R. E. Batalov; A. A. Andreev; S. V. Popov (Российский кардиологический журнал, 2022)
The paper presents a description of the diagnosis and treatment of takotsubo syndrome in a patient with paroxysmal atrial fibrillation after electrical cardioversion. A case report clearly reflects the need for an integrated diagnostic approach to verify the diagnosis using dynamic echocardiography, electrocardiography, angiographic and tomographic investigations. The complexity of differential diagnosis in this case was an atypical variant of myocardial dysfunction. Follow-up made it possible to track the clinical improvement of the patient and the almost complete normalization of myocardial contractility in terms characteristic of takotsubo syndrome.